HUBUNGAN PELAKSANAAN FUNGSI KEPALA DESA TERHADAP KETERPILIHAN NAZARUDDIN SEBAGAI KEPALA DESA SUNGAI SEBESI KECAMATAN KUNDUR KABUPATEN KARIMUN TIGA PERIODE TAHUN 2008-2022 - ', Tendryabeng; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The village head is the highest position in the village. The election of the village head is a democratic party, because the local community can actively participate in selecting candidates who will be responsible for developing the village. Therefore, the election of the village head is very important because it greatly supports the implementation of village governance. Law No. 6/2014 states that a person may hold the position of village head for three periods, either consecutively or non-consecutively. Thus, a person may maintain his or her position as Village Head for 18 years, with each period lasting six years. Nazaruddin is the Village Head of Sungai Sebesi who has been elected three times in a row for three periods, namely in 2008, 2013, and 2022. The research approach used is a quantitative approach. The research location is in Sungai Sebesi Village, Kundur District, Karimun Regency, Riau Islands. The types and sources of research data are divided into primary data with data collection techniques from the results of questionnaires / surveys distributed at the research location and secondary data in the form of data that is already available, such as Village RPJM, Policy Data that has been implemented, the number of voters in the Sungai Sebesi PILKADES, the number of votes, and other data related to this research. The result of this research is that in the field of village development, the highest score is the construction of clean water facilities with a score of 352. In the field of village community development, the religious competition program for children held on every religious holiday with a score of 383. In the field of village community empowerment, the BIMTEK program for nursery planting and pineapple marketing scored 341. The field of village government administration is the village office construction program with a score of 366. These programs have been implemented against the village and show that Nazaruddin has carried out the main duties of a village head according to Law Number 6 of 2014. So that an incumbent village head can maintain his position. Keywords : village head duties, village head election, incumbent